Ameliorative Effects of Indigenous Medicinal Plants against Hepatic Diseases in Southern Region of India- A Review - K, Pugazhendy; P, Sasikala (Asian Journal of Pharmaceutical Research and Development, 2021)
Purpose: Liver is an important part in human beings and plays a major role in metabolism and excretion of xenobiotics from the body. Selection of Data: Further, hepatotoxicity is caused by different types of toxic chemicals, such as antibiotics, and chemotherapeutic agents like paracetamol (C8H9NO2), thioacetamide (C2H5NS), carbon tetrachloride (CCl4), silymarin (C25H22O10), ethanol (C2H5OH), and excessive alcohol in taking and microbes are well researched. The markedly available synthetic drugs to treat liver sickness in this condition also cause further damage to the liver. Hence herbal medicines have being become popularize and their utilized is wide-spread. In plant derived drugs have been utilized in the treatment of liver diseases for a long time and to protect a healthy liver. Liver injury induced by toxins is more common now-a-days. Herbal remedies are focused in the pharmaceutical industry to evolve a safe route for liver disorders and which is very low prize and also no side effects compared with synthetic drugs. Conclusion: Hence an attempt has been made to reviewed and compiled the available data on photochemical from medicinal plants that have tested in hepatoprotective models using modern scientific system. For the present investigation the selected plants are Avicennia alba, Anisochilus carnosus Baliospermum montanum, Centella asiatica, Clitoria ternatea, Eclipta alba, Justicia adhatada, Phyllanthus emblica, Pisonia Grandis and Syzgium cumini .